Effects of Bisphosphonates Treatments in Osteopenic Older Women: A Systematic Review and Meta-Analysis - Li, Jiangbi; Sun, Yang; Chen, Zhuo; Xie, Xiaoping; Gu, Feng; Bi, Songqi; Yu, Tiecheng (Frontiers in Pharmacology, 2022)
Aims: To review the effects of bisphosphonates on bone density, fractures, and bone markers in osteopenic older women. Methods: Relevant articles published before February 2022 were searched in PubMed, EMBASE, and the Cochrane Library. All randomized controlled trials that reported incident fractures, bone mineral density (BMD), bone markers, or adverse events with bisphosphonates in osteopenic older women were included. The quality of included studies was assessed using the Cochrane Risk of Bias tool. The risk ratios (RRs) for fractures, net percent change in bone mineral density and differences in bone markers were calculated using a meta-analysis. Results: A total of 11 studies were included in our meta-analysis. Bisphosphonates significantly increased the percent changes in the lumbar spine BMD (WMD, 5.05; 95% CI, 3.21 to 6.88; I2=98.4%), hip BMD (WMD, 4.80; 95% CI, 2.93 to 6.66; I2=97.1%), total body BMD (WMD, 3.24; 95% CI, 2.12 to 4.35; I2=90.9%), femoral neck BMD (WMD, 4.02; 95% CI, 1.70 to 6.35; I2=91.8%) and trochanter BMD (WMD, 5.22; 95% CI, 3.51 to 6.93; I2=83.6%) when compared to placebo. Zoledronate was associated with a great treatment effect on fragility fracture (RR, 0.63; 95% CI, 0.50 to 0.79), clinical vertebral fracture (RR, 0.41; 95% CI, 0.22 to 0.76), and radiographic vertebral fracture (RR, 0.60; 95% CI, 0.27 to 1.35) compared to placebo. Meanwhile, alendronate was also associated with beneficial effects on fragility fracture (RR, 0.40; 95% CI, 0.15 to 1.07), clinical vertebral fracture (RR, 0.46; 95% CI, 0.17 to 1.24), and radiographic vertebral fracture (RR, 0.64; 95% CI, 0.38 to 1.09). In addition, the use of bisphosphonates reduced the concentration of procollagen type I N-terminal propeptide (PINP) and C-terminal telopeptide of type I collagen (CTX) over placebo by 15.79 (95% CI, -18.92 to -12.66; I2=28.4%), -0.23 (95% CI, -0.35 to -0.10; I2=91.3% ), respectively. Conclusion: All bisphosphonates examined were associated with beneficial effects on fractures, BMD, and bone markers in women with osteopenia. Further randomized controlled trials are necessary to clarify the safety of bisphosphonates in women with osteopenia.